2018
DOI: 10.1111/jorc.12247
|View full text |Cite
|
Sign up to set email alerts
|

Kidney symptom questionnaire: Development, content validation and relationship with quality of life

Abstract: This work has provided a new, validated symptom score for patients with CKD not requiring RRT for clinical management and research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
(72 reference statements)
1
14
1
Order By: Relevance
“…According to Mallamaci et al [12], exercise suggests a beneficial effect on physical performance and health endpoints which are achieved by improvement in aerobic and walking capacity. The results of the survey (HEM preday : 0:82 ± 0:94, HEM day : 0:95 ± 0:83, and HEM postday : 1:41 ± 1:82, km/day) are not in line with those of Brown et al [7] who reported a decrease in patients' physical activity after hemodialysis. However, the findings of the research are in line with those of Bonner et al [13] who showed the strong influence of the disease on work, daily life, and in general the lifestyle of patients while at the same time identifying differences between them due to their different lifestyles.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…According to Mallamaci et al [12], exercise suggests a beneficial effect on physical performance and health endpoints which are achieved by improvement in aerobic and walking capacity. The results of the survey (HEM preday : 0:82 ± 0:94, HEM day : 0:95 ± 0:83, and HEM postday : 1:41 ± 1:82, km/day) are not in line with those of Brown et al [7] who reported a decrease in patients' physical activity after hemodialysis. However, the findings of the research are in line with those of Bonner et al [13] who showed the strong influence of the disease on work, daily life, and in general the lifestyle of patients while at the same time identifying differences between them due to their different lifestyles.…”
Section: Discussioncontrasting
confidence: 81%
“…Abstinence from professional activities is also an important parameter in patients' lives, and their inability to meet their obligations creates feelings of impotence. The requirement to stay in the artificial kidney for several hours daily does not obviously allow patients to work normally and fall short of even light weight work capacity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 11-item Leicester Uraemic Symptom Scale (LUSS) [21, 22] evaluated the number, frequency (0 = ‘never’ to 4 = ‘every day’) and intrusiveness (symptom impact) (0 = ‘not at all intrusive’ to 4 = ‘extremely intrusive’) of uraemic symptoms. Each individual symptom was scored out of four, and summative scores were generated: Total symptom number (LUSS-1): total number of symptoms experienced (out of 11).Total symptom frequency score (LUSS-2): frequency of each 11 symptoms rated 0–4 (out of 44).Total symptom intrusiveness score (LUSS-3): perceived intrusiveness of each 11 symptoms rated 0–4 (out of 44).…”
Section: Methodsmentioning
confidence: 99%
“…The LUSS has been widely used to determine symptom burden in renal populations [7, 12, 19, 21] and has recently been validated by our group [22].…”
Section: Methodsmentioning
confidence: 99%